2010
DOI: 10.1111/j.1524-4725.2009.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualized Sclerotherapy of Varicose Veins

Abstract: Our new method not only avoids the risk of radiation exposure, but also allows for simple observation of sclerosant range of access, determination of the dosage for each lesion, and accurate administration of therapy to target lesions. This method will contribute to further advances in sclerotherapy, given that it allows administration of sclerosant and visual confirmation of optimal injection dosage, speed, and movement of sclerosant after injection. The authors have indicated no significant interest with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…In total, 35 patients were treated and studied. In all patients, sclerosant spreading was seen as excellent, and no side effects from ICG were observed [148]. …”
Section: Surgical Applicationsmentioning
confidence: 99%
“…In total, 35 patients were treated and studied. In all patients, sclerosant spreading was seen as excellent, and no side effects from ICG were observed [148]. …”
Section: Surgical Applicationsmentioning
confidence: 99%
“…ICG (Diagnogreen for injection; Daiichi‐Sankyo Co. Ltd., Tokyo, Japan) was used as an NIR fluorophore. Concentrated ICG solution (0.04 mL) was made by dissolving ICG (25 mg) in injection solvent (10 mL) and added to 10 mL of sclerosant solution, resulting in an ICG concentration of 0.01 mg/mL . The sclerosants were absolute ethanol and 3% polidocanol (Polidocasklerol 3% injection; Zeria Pharmaceutical Co., Ltd., Tokyo, Japan) foamed using the Tessari method .…”
Section: Methodsmentioning
confidence: 99%
“…6 Kikuchi and Hosokawa reported that intraoperative NIR fluorescence imaging allowed for visualization of sclerosant spreading in varicose veins. 7 We used a real-time NIR fluorescence imaging system with indocyanine green (ICG) as an additional monitor of the spread of sclerosant in duplex-guided percutaneous sclerotherapy of soft-tissue venous malformations. In this report, we describe our clinical experience and evaluate the safety and efficacy of NIR fluorescence imaging.…”
mentioning
confidence: 99%
“…The camera is portable and maneuverable, and yields digitized, real-time images. 87 It has been developed for indications such as visualization of sentinel lymph nodes/tumors in cancer patients [88][89][90] and visualization of the sclerosant polidocanol during sclerotherapy in sclerotic veins. 87 Piwkowski et al 91 demonstrated the efficacy of this technology for assessment of intercostal muscle blood perfusion in a pilot study of patients undergoing pulmonary resection.…”
Section: Photodynamic Eye™mentioning
confidence: 99%